2011
DOI: 10.1016/j.ajpath.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Endothelium-Pericyte Cross Talk by Inhibiting VEGF Receptor Signaling Attenuates Kidney Microvascular Rarefaction and Fibrosis

Abstract: Microvascular pericytes and perivascular fibroblasts have recently been identified as the source of scar-producing myofibroblasts that appear after injury of the kidney. We show that cross talk between pericytes and endothelial cells concomitantly dictates development of fibrosis and loss of microvasculature after injury. When either platelet-derived growth factor receptor (R)-␤ signaling in pericytes or vascular endothelial growth factor (VEGF)R2 signaling in endothelial cells was blocked by circulating solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
295
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(314 citation statements)
references
References 44 publications
15
295
1
3
Order By: Relevance
“…PDGFRβ/PDGF-BB is the main signalling pathway mediating pericyte recruitment during vessel development (Hellstrom et al, 1999). This same pathway has been reported in the recruitment of pericytes to injured tissue, where they eventually contribute to fibrosis in organs such as the lung (Hung et al, 2013) and kidney (Humphreys et al, 2010;Lin et al, 2011;Schrimpf et al, 2012). Activated pericytes have been shown to detach from local capillaries, migrate to the site of injury and differentiate into myofibroblasts (Goritz et al, 2011;Lin et al, 2011;Ren et al, 2013).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurysupporting
confidence: 59%
See 1 more Smart Citation
“…PDGFRβ/PDGF-BB is the main signalling pathway mediating pericyte recruitment during vessel development (Hellstrom et al, 1999). This same pathway has been reported in the recruitment of pericytes to injured tissue, where they eventually contribute to fibrosis in organs such as the lung (Hung et al, 2013) and kidney (Humphreys et al, 2010;Lin et al, 2011;Schrimpf et al, 2012). Activated pericytes have been shown to detach from local capillaries, migrate to the site of injury and differentiate into myofibroblasts (Goritz et al, 2011;Lin et al, 2011;Ren et al, 2013).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurysupporting
confidence: 59%
“…This same pathway has been reported in the recruitment of pericytes to injured tissue, where they eventually contribute to fibrosis in organs such as the lung (Hung et al, 2013) and kidney (Humphreys et al, 2010;Lin et al, 2011;Schrimpf et al, 2012). Activated pericytes have been shown to detach from local capillaries, migrate to the site of injury and differentiate into myofibroblasts (Goritz et al, 2011;Lin et al, 2011;Ren et al, 2013). However, the recruitment of pericytes following injury and their collagen-producing capacity may be dependent on both the type of injury and the tissue under investigation (Birbrair et al, 2014a;Nakagomi et al, 2011).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurymentioning
confidence: 54%
“…One possible mechanism for this, as mentioned above, is through the PDGF/PDGFRβ axis. Signaling through this pathway results in a potent chemotactic and mitogenic response seen in pericyte recruitment, both during development 69, 70, and following tissue injury 71, 72. In cell culture, it has been reported that amniotic epithelial cells produce PDGF‐B 73, 74, and therefore, could potentially serve as a stimulus for perivascular migration in vivo.…”
Section: Are Wharton's Jelly Mscs Perivascular In Origin?mentioning
confidence: 99%
“…Kidney endothelial cells may promote fibrosis by expression of ECM, as suggested in experimental diabetic nephropathy (206) or via a crosstalk with interstitial cells (207). Apart from proangiogenic growth factors (150), several proteins have been suggested to play a role in endothelial cell remodeling leading to fibrosis including ephrin-B (208), Crim-1 (209), Id proteins (210), miR-126 (211), and the glycocalyx of glomerular endothelial cells (212).…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%